2018
DOI: 10.1016/j.biomaterials.2018.07.037
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable synthetic graft for small arteries matches the performance of autologous vein in rat carotid arteries

Abstract: Autologous veins are the most widely used grafts for bypassing small arteries in coronary and peripheral arterial occlusive diseases. However, they have limited availability and cause donor-site morbidity. Here, we report a direct comparison of acellular biodegradable synthetic grafts and autologous veins as interposition grafts of rat carotid arteries, which is a good model for clinically relevant small arteries. Notably, extensive but transient infiltration of circulating monocytes at day 14 in synthetic gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 65 publications
3
57
1
Order By: Relevance
“…[ 1–7 ] Of particular interest in our lab is to engineer an acellular fast‐degrading PGS vascular graft for small‐diameter arteries. [ 8–14 ] The synthetic graft is fully remodeled by host cells in months post‐implantation. The neo‐tissue possesses extracellular matrix (ECM), architecture and performance resembling to the native arteries as demonstrated in rat abdominal aorta and carotid models.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–7 ] Of particular interest in our lab is to engineer an acellular fast‐degrading PGS vascular graft for small‐diameter arteries. [ 8–14 ] The synthetic graft is fully remodeled by host cells in months post‐implantation. The neo‐tissue possesses extracellular matrix (ECM), architecture and performance resembling to the native arteries as demonstrated in rat abdominal aorta and carotid models.…”
Section: Introductionmentioning
confidence: 99%
“…Shinoka et al used a 50:50 poly (L-lactic-co-ε-caprolactone) (PLCL) copolymer graft as an inner layer, and two different compositions outer layer, slow-degrading PLA and fast-degrading PLA + PGA, respectively. 90.5% (19/21) PGS-PCL grafts were patent in rat carotid arteries interposition model as long as 3 months, and no statistical difference was found between the PGS-PCL grafts and the autologous external jugular vein grafts (Lee et al, 2018). The fast-degrading grafts showed greater cell infiltration in the outer layer with significantly less calcification than slow-degrading grafts, and all 10 grafts kept patent, although endothelialization and SMC proliferation were comparable (Sugiura et al, 2017).…”
Section: Biodegradable Synthetic Polymersmentioning
confidence: 91%
“…Hemocompatibility tests showed that PGS had low platelet adhesion and inflammation, and stimulated the production of elastin (Lee et al, 2018;Motlagh, Yang, Lui, Webb, & Ameer, 2006). However, the clinical performance of synthetic grafts was poor, associated with low patency and high thrombus formation.…”
Section: Biodegradable Synthetic Polymersmentioning
confidence: 99%
See 2 more Smart Citations